# 7-2(x+3)=9(x-1)

## Simple and best practice solution for 7-2(x+3)=9(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 7-2(x+3)=9(x-1) equation:

Simplifying
7 + -2(x + 3) = 9(x + -1)
Reorder the terms:
7 + -2(3 + x) = 9(x + -1)
7 + (3 * -2 + x * -2) = 9(x + -1)
7 + (-6 + -2x) = 9(x + -1)
Combine like terms: 7 + -6 = 1
1 + -2x = 9(x + -1)
Reorder the terms:
1 + -2x = 9(-1 + x)
1 + -2x = (-1 * 9 + x * 9)
1 + -2x = (-9 + 9x)
Solving
1 + -2x = -9 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
1 + -2x + -9x = -9 + 9x + -9x
Combine like terms: -2x + -9x = -11x
1 + -11x = -9 + 9x + -9x
Combine like terms: 9x + -9x = 0
1 + -11x = -9 + 0
1 + -11x = -9
Add '-1' to each side of the equation.
1 + -1 + -11x = -9 + -1
Combine like terms: 1 + -1 = 0
0 + -11x = -9 + -1
-11x = -9 + -1
Combine like terms: -9 + -1 = -10
-11x = -10
Divide each side by '-11'.
x = 0.9090909091
Simplifying
x = 0.9090909091`